2023
DOI: 10.1108/jfep-01-2023-0012
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion and financial performance: evaluating the moderating effect of mandatory corporate social responsibility

Abstract: Purpose This study aims to examine the nexus among financial inclusion, legislative corporate social responsibility (CSR) and the financial performance of banking companies in India. Design/methodology/approach The study uses the fixed-effect model to measure the impact of financial inclusion on the financial performance of banks listed in the Bank Nifty Index from 2015 to 2022. Furthermore, it examines the interaction effect of legislative CSR and financial inclusion on the performance of banks. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Odugbesan et al (2022) affirm that financial inclusion and development indeed promote sustainable development among sub-Saharan African countries. Bhatter and Chhatoi (2023) analyze the interplay between financial inclusion, financial performance and mandatory corporate social responsibility, identifying potential synergies. Inoue (2019) contributes insights by examining the impact of financial inclusion on poverty reduction in India, illuminating the role of inclusive finance in mitigating poverty.…”
Section: Theoretical Relevance Empirical Evidence and Hypotheses Form...mentioning
confidence: 99%
See 1 more Smart Citation
“…Odugbesan et al (2022) affirm that financial inclusion and development indeed promote sustainable development among sub-Saharan African countries. Bhatter and Chhatoi (2023) analyze the interplay between financial inclusion, financial performance and mandatory corporate social responsibility, identifying potential synergies. Inoue (2019) contributes insights by examining the impact of financial inclusion on poverty reduction in India, illuminating the role of inclusive finance in mitigating poverty.…”
Section: Theoretical Relevance Empirical Evidence and Hypotheses Form...mentioning
confidence: 99%
“…Odugbesan et al (2022) affirm that financial inclusion and development indeed promote sustainable development among sub-Saharan African countries. Bhatter and Chhatoi (2023) analyze the interplay between financial inclusion, financial performance and mandatory corporate social responsibility, identifying potential synergies.…”
Section: Theoretical Relevance Empirical Evidence and Hypotheses Form...mentioning
confidence: 99%
“…Fourth, financial inclusion helps the monetary authority control inflation (Mbutor and Uba, 2013; Mehrotra and Nadhanael, 2016). At the same time, financial inclusion also causes financial stability and contributes to growth indirectly (Sethi and Sethy, 2019; Saha and Dutta, 2022; Sethy and Goyari, 2022; Bhatter and Chhatoi, 2023). In contrast, Sahay et al (2015) reported financial inclusion doesn't guarantee financial stability.…”
Section: Theoretical Frameworkmentioning
confidence: 99%